Variations in administration of Covid-19 vaccine during last 20 weeks at a vaccination center of Agra, Uttar Pradesh - Chaudhary, Shailendra Singh; Nagargoje, Manisha Madhukar; Singh, Himalaya; Singh, Kunver Viresh; Kumar, Rinu; Sayeed, Waqaar (Indian Journal of Community Health, 2021)
Background: Covid-19 pandemic has created havoc around the world and vaccination is an effective tool against this demon. Study of variations in administration of daily doses of Covid-19 vaccine at vaccination centre can help in better resource management. Material & methods: This record based descriptive study was conducted among beneficiaries of Covid-19 vaccination at S. N. Medical College, Agra. Record of administration of daily doses and vaccine wastage, vaccination of different groups of beneficiaries and occurrence of various national and local events related to vaccination was also analyzed. Result: A total of 33,571 doses of any Covid-19 vaccine (Covaxin/Covishield) were administered during past 88 working days in 20 weeks expanded over 5 months. On an average 165 doses were administered every day by each team and overall vaccine wastage was 0.85%. Maximum average of 199 doses per day by each team was observed on Mondays. There are many peaks and drops in administration of daily doses of Covid-19 vaccine at our center which can be attributed to either some national or local events related to supply of vaccine at our center, addition of a new group of beneficiary, any news or political controversy related to Covid-19 vaccination etc. Conclusion: Understanding of spikes and drops in the curve of daily/weekly administration of Covid-19 vaccine, in view of occurrence of various national and local events related to vaccination, can help in better formulation of strategies specially related to human resource allocation for success of National Covid-19 vaccination program.